Efficiency and productivity to social welfare: the case of the main forestry-producing micro-regions in Brazil - Jessica Suarez Campoli; Paulo Nocera Alves Junior; Tatiana Kimura Kodama; Marcelo Seido Nagano; Heloisa Lee Burnquist (Revista de Economia e Sociologia Rural)
Abstract The studies on the forest sector focus on energy issues and environmental challenges, but they are limited to a small number of studies focused on economic growth and social welfare. In the forest sector, Brazil is among the five countries with large forest cover in the world, with favorable conditions and great potential for production growth. Therefore, this work aimed to measure the evolution of efficiency and productivity of the 49 Brazilian forestry microregions in converting the expansion of economic growth into social welfare from 2009 to 2015 (a period of sectoral growth in the country). The approach of the Slack-Based Measure (SBM) – Data Envelopment Analysis (DEA), Malmquist Productivity Index (MPI), and Windows Analysis model was combined, followed by a solution for infeasibility problems. The results show that the growth of the forestry sector was not accompanied by the Human Development Index (HDI) in most of the microregions, showing regional and state differences, with the microregions close to the sensitive environmental areas with the lowest HDI. Thus, the work contributes to the design of public policies and government decision-making to increase the sector's efficiency and productivity and to social indicators that can guide sustainable policies in other contexts and countries.